EFFECT OF ADDING ARTICHOKE LEAVES EXTRACTPOWDER (CYnarascolymus L.) TO THE DIET ON THE PRODUCTIVE PERFORMANCEOFBROILERS. - Al- Masari, A.I.; Al-Himdany, H.Q. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted at the poultry farm Animal Production Department, Abu Ghraib , College of Agricultural Engineering Sciences, University of Baghdad, during theperiod from 10/31/2020 to 12/11/2020. to study the effect of adding two different levels of artichoke leaves extracts powder to the diet and for different periods to rations on the productive performance of broiler chickens.One hundred thirty five unsexedcommercial hybrid broiler chicks (Ross 308), oneday old, 42.47 g/ its initial body weightwere used in this experiment, The birds were randomly distributed among three treatments, each treatment contained 45 birds, with three replicates, and each replicate contained 15 birds. The chicks of the first treatment (T1) were fed a standard diet for broilers free of addition, while the chicks of the T2 and T3 treatment were fed a standard diet for broilers in addition to the artichoke leaves extract powder at a levels 0.5 and 1 g/kg diet respectively. The results obtainedindicated that adding artichoke leaves extract powder at two different levels to broiler diets led to a significant (P<0.05) superiority (P<0.05) for treatment T2 and T3 in the productive performance of body weight rates compared to the control treatment. In the average cumulative weight gain 1-6 week compared to the control treatment (T1), the T3 treatment also recorded a significant (P<0.05)increase superiority (P<0.05) in the amount of cumulative feed consumption and feed conversion factor compared to the treatment T1, T2, In conclusion, the resultsindicate that supplementing artichoke leaves extractpowder to the diet showed a ssignificantin Improving in the productiveperformance of broiler.